Correction to: Predation capacity of phytoseiid mites (Mesostigmata: Phytoseiidae) from Brazil on eggs of Diaphorina citri (Hemiptera: Liviidae) (Phytoparasitica, (2021), 10.1007/s12600-021-00898-9) - Jorge, Sofía Jiménez [UNESP]; Rueda-Ramírez, D.; de Moraes, G. J. (Springer Nature, 2021)
The original version of this article unfortunately contained an incorrect presentation of author name. S. Jiménez Jorge should be Sofía Jiménez Jorge.